The Changes in Chemical and Physical Properties of Fibric Peat Pollowing Burning - B.H Saharjo; A.D Nurhayati (Jurnal Ilmu Tanah dan Lingkungan, 2003)
Fire is still used until today for land preparation because it is cheap, easy and relatively quick to be done, meanwhile, the impact is still not much yet known especially for peatland Due to that reason the research, especially on peat quality following burning, is highly important in order to understand the performance of it in the term of sustainability. The research objective was to understand the performance of burned peat quality compared to the condition before burning at fibric peat especially in the land preparation area using fire belong to the shifting cultivator. The site was located in the Pelalawan district, Riau province, Indonesia, during the dry season in the year 2001. To reach the research objective 2 plots of each 400 m) (20 m x 20 m) were established. The results of the research shown that soon the following burning, chemical properties of burned peat were increased significantly, while after one month part of them tended to decrease such as P, K, and base saturation. Three months after burning most of the chemical properties decreased while at six months a few of them were still increased such as P, Na and CEC. This research showed that the increasing of ash after burning was a temporary effect and others the negative impact is continued. Key words: fire, peat burning, peat quality